2020
DOI: 10.1177/0021998320938836
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic interference of nickel ferrite and copper ferrite filled low-density polyethylene composite

Abstract: This study reports the preparation of nickel ferrite (NiFe2O4) and copper ferrite (CuFe2O4) filled low-density polyethylene (LDPE) composite through a melt mixing process for employing in electromagnetic shielding applications. The X-Ray diffraction (XRD) with different pH values 6, 8 and 10 resulted the formation of cubic structure for NiFe2O4 of cristallite size 21 nm, 25 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The diffused carbon with nickel as alloying elements are homogenization with inter dendrite grain boundaries at lower temperature having non-uniformity delivers lack in both mechanical and metallurgical properties on coating, later cored structure iron improves those properties. 21 Electrical conductivity deserves the structure that presents in the coating copper together with nickel having higher solute in metal that dissolves in to carbon that increases deposition efficiency up to 25% for nickel and copper at range to 15% remains other elements hold other mechanical properties like hardness, toughness, tensile strength etc., is detailed in Figure 5(c) with its thickness variation across in Figure 5(d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffused carbon with nickel as alloying elements are homogenization with inter dendrite grain boundaries at lower temperature having non-uniformity delivers lack in both mechanical and metallurgical properties on coating, later cored structure iron improves those properties. 21 Electrical conductivity deserves the structure that presents in the coating copper together with nickel having higher solute in metal that dissolves in to carbon that increases deposition efficiency up to 25% for nickel and copper at range to 15% remains other elements hold other mechanical properties like hardness, toughness, tensile strength etc., is detailed in Figure 5(c) with its thickness variation across in Figure 5(d).…”
Section: Resultsmentioning
confidence: 99%
“…The variation in loading condition show similar other mechanism like grinding of groves, pits, pull outs, wear debris are common are disclosed in previous research. 16,1822…”
Section: Resultsmentioning
confidence: 99%
“…The sample material with material and without material was fixed at two ends of the sample port holder. Already reported in our work 24 thereafter the VNA is connected with these two end port cables. The incident electromagnetic wave was in some measure reflected, absorbed and, transmitted through the medium.…”
Section: Emi Shieldingmentioning
confidence: 91%
“…A lot of works have been devoted to the fabrication and investigation of polymer composites with incorporated carbon based fillers 12‐17 or ferrites 18‐21 . The results revealed that such composites can be used as efficient EMI shields.…”
Section: Introductionmentioning
confidence: 99%